Examining the overarching factors of clients' loyalty based on the mobile insurance typology - Enock M. Ampaw; Junwu Chai; Joseph Frempong (South African Journal of Business Management, 2019)
Background: The mobile insurance industry plays a crucial role in the insurance ecosystem of developing countries, yet the overarching factors that impinge on and shape clients' behavioural intentions towards service providers have not been given the necessary attention they deserve.Objectives: This study explores the role of corporate identity, clients' satisfaction, Service Quality (SERQUAL) and institutional-based trust in shaping clients' loyalty (CL) towards mobile insurance (M-insurance) service providers.Method: Structural equation modelling (SEM) was used to analyse a total of 334 questionnaires obtained from clients of selected M-insurance service points in Accra, Ghana.Results: Our results indicate that SERQUAL, institutional-based trust, satisfaction and corporate identity, corroboratively, impact positively on CL within the M-insurance ecosystem, albeit in varied proportions. The results also demonstrate a high degree of causality among SERQUAL, institutional-based trust and corporate identity.Conclusion: SERQUAL has both direct and indirect significant positive relationships with CL. Thus, in order for M-insurance service providers to attract and retain clients, the former must pay a great deal of attention to SERQUAL owing to its striking halo effects.
Keywords: 650